Take and Give Learning on Cooperation Skills Cooperation Skills in Civics Subjects in Class III of Istana Hati Private Elementary School - Ananda Marpaung, Puput (Journal of General Education Science, 2023)
This study aims to determine the effect of the take and give learning model on the cooperation skills of third grade students in Civics Education subjects at Istana Hati Elementary School, Binjai City. The location of this research was at Istana Hati Private Elementary School in North Binjai. This research was conducted in March - April 2023. This research method uses experimental research by measuring the effect of the learning model from the pretest and postest scores on the ability to cooperate with students from the questionnaire results. The population and sample in this study were all third grade students of Istana Hati Elementary School as many as 28 people. The results of this study are that there is an effect of the take and give learning model on the skills of working together with third grade students in Civics Subjects at Istana Hati Elementary School, Binjai City. This means that the conclusion from the results of the pretest and postest value hypothesis test is that there is an effect of the take and give learning model on student pretests and postests. As well as the results of hypothesis testing as well as the results of the last hypothesis of thisstudy,namelyobtainedrhitung >rtabelor41.251>2.9019thenH0isaccepted.Thismeans that the conclusion from the results of the hypothesis test on the value of students' cooperation skills is that there is an effect of the take and give learning model on students' cooperation skills in Civics lessons for third grade students of Istana Hati Elementary School, Binjai City.